UPAYA MENINGKATKAN KOMPETENSI GURU SDN 020 LANGSAT HULU DALAM MENYUSUN PENILAIAN PROSES K13 MELALUI SUPERVISI AKADEMIK - Marjoni Marjoni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The ability of teachers to implement curriculum 13 greatly influences the success of learning. The research aims to improve the ability of teachers to prepare an assessment of the K13 process through academic supervision. The research method in this study is School Action Research which consists of planning, action, observation, and reflection. This research was conducted at SDN 020 Langsat Hulu Kec. Sentajo Raya Kab. Kuantan Singingi. The research subjects were 10 teachers, consisting of 2 men and 8 women teachers. The results showed that academic supervision can improve teacher competency in compiling the assessment of the learning process with an average learning process in the first cycle of 79% which was included in the sufficient category, and experienced an increase in the second cycle to 84.5% with good categories. The conclusion is that the teacher's ability to conduct process assessments has increased with good categories.